2022
DOI: 10.1021/acsenergylett.2c02385
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Redox Shuttle Explains Voltage-Induced Halide Redistribution in Mixed-Halide Perovskite Devices

Abstract: Voltage-induced halide segregation greatly limits the optoelectronic applications of mixed-halide perovskite devices, but a mechanistic explanation behind this phenomenon remains unclear. In this work, we use electron microscopy and elemental mapping to directly measure the halide redistribution in mixed-halide perovskite solar cells with quasi-ion-impermeable contact layers under different bias polarities to find iodide and bromide accumulation at the cathode and anode, respectively. This is consistent with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…This could be due to a number of factors discussed as follows: (i) the larger I – ion possesses a much greater polarizability, which produces a large internal field to counter the external applied bias, and leads to lower charge carrier mobility . (ii) The use of an inert (FTO) anode along with Ag cathode leads to the formation of a redox shuttle of the halide ion across the absorber (Figure a), which leads to charge carrier (electron/hole) capture and reduced mobility . This effect would be much more pronounced for the larger I ions moving through 5 μm thick films.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be due to a number of factors discussed as follows: (i) the larger I – ion possesses a much greater polarizability, which produces a large internal field to counter the external applied bias, and leads to lower charge carrier mobility . (ii) The use of an inert (FTO) anode along with Ag cathode leads to the formation of a redox shuttle of the halide ion across the absorber (Figure a), which leads to charge carrier (electron/hole) capture and reduced mobility . This effect would be much more pronounced for the larger I ions moving through 5 μm thick films.…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to a number of factors as stated below: (i) the use of Ag for both cathode and anode, instead of the FTO cathode with a charge transporting layer, forms an electrode–absorber interface with a different injection barrier as compared to the transporting layer (Figure S13). (ii) The Ag anode acts to suppress halide oxidation and therefore the mobile halide ion redox shuttle observed in the thick film devices (Figure b) . This reduces the level of charge carrier capture by mobile halide ions and enhances their mobility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we studied voltage-induced halide segregation probed by PL peak shifts and cross-sectional scanning transmission electron microscopy–energy-dispersive X-ray spectroscopy (STEM–EDX). We found that iodine photo-electrochemistry and iodine transport pathways play important roles in halide segregation for mixed iodide/bromide perovskites, with an organic hole transport layer (HTL) providing a fast external iodine transport pathway, which depends strongly on ionization energy (IE). Since HTLs with different highest occupied molecular orbital (HOMO) levels show drastically different iodine diffusion rates, it is expected that different HTLs may have different effects on light-induced halide segregation. Therefore, an in-depth study on how different HTLs affect light-induced halide segregation is necessary for the design of stable mixed-halide perovskite-based optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the pure-red perovskite emitters can be conveniently approached by halide substitution to generate Br–I mixed perovskites . However, the mixed halide perovskites suffer from severe ion migration during device operation, leading to spectral instability that significantly limits their further commercialization. …”
mentioning
confidence: 99%